2006
DOI: 10.1177/103841620601500107
|View full text |Cite
|
Sign up to set email alerts
|

Counsellor Practices and Student Perspectives: Perceptions of Career Counselling in Australian Secondary Schools

Abstract: A u s t r a l i a n J o u r n a l o f C a r e e r D e v e l o p m e n t Vo l u m e 5 , N u m b e r , Au t u m n 2 0 0 6 I ncreasing focus by both state and federal governments in Australia on the post-school outcomes of students has resulted in a range of developments and policies. These have been aimed at attracting and retaining students in educational settings and equipping them to make choices about their future career and education. The Queensland Certificate of Education (Queensland Studies Authority, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 2 publications
1
28
0
Order By: Relevance
“…12,19 Career advisors can play an important role in students' career decisions and the information they provide to students can influence their potential career choices. 7,9,10 Our study indicated that almost two thirds of respondents had received requests about pharmacy as a career in the previous 5 years. Therefore, having accurate, informative resources about pharmacy courses and career paths easily accessible to career advisors is essential.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…12,19 Career advisors can play an important role in students' career decisions and the information they provide to students can influence their potential career choices. 7,9,10 Our study indicated that almost two thirds of respondents had received requests about pharmacy as a career in the previous 5 years. Therefore, having accurate, informative resources about pharmacy courses and career paths easily accessible to career advisors is essential.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,7 Furthermore, students themselves have reported that career advisors are a useful resource when it comes to career decision-making. [7][8][9][10][11] Not surprisingly, students prefer career advisors who are proactive in seeking them out, rather than career advisors who rely on students to initiate contact with them. 10 Students also prefer career advisors who adopt a student-centered approach, although information-centered approaches, which include written materials and group talks, are also valued.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations